Diagnostic value of serum amyloid A in differentiating the inflammatory disorders in wild birds - Rhim, Haerin; Kim, Myeongsu; Gim, Seulgi; Han, Jae-Ik (Frontiers in Veterinary Science, 2024)
Rescued wild birds have very high rates of inflammatory diseases; however, there have been limitations in assessing them sensitively. Few studies have examined acute-phase proteins in wild birds. In this study, serum amyloid A (SAA) was evaluated as an inflammatory indicator along with traditional indices such as white blood cell count, albumin, and albumin/globulin ratio. In total, 291 samples from 139 birds of six avian species were analyzed. All samples were divided into four groups (severe, moderate, mild injuries, and clinically healthy) based on clinical examinations and evaluated by group. SAA levels were measured using an anti-chicken SAA ELISA kit and compared with leukocyte counts, albumin concentrations, and albumin/globulin ratios. Differences among groups were evaluated using the Kruskal–Wallis test, followed by a post hoc test using Dunn’s multiple comparisons with SPSS V27. Statistical significance was set at a value of p of <0.05. The median concentration and interquartile range (ng/mL) of SAA in each group were 78.10 ng/mL (50.71–109.30), 31.15 ng/mL (19.85–49.24), 9.68 ng/mL (4.71–22.06), and 3.10 ng/mL (1.50–6.00). We observed a significant difference in the mean levels between the groups (p < 0.001), with the same results observed across species. All four indices showed significant differences in mean values between the groups (p < 0.001). In addition, SAA showed rapid changes in periodically collected samples, reflecting either a positive treatment response or the onset of subclinical diseases. SAA can be used to detect inflammatory conditions and asymptomatic disease in wild birds and is helpful in accurately identifying current health status, which is essential for successful treatment and release.